Stable Fe isotope fractionation during dissimilatory Fe(III) reduction by a thermoacidophile in acidic hydrothermal environments. (1st January 2021) - Chanda, Piyali; Amenabar, Maximiliano J.; Boyd, Eric S.; Beard, Brian L.; Johnson, Clark M.
Abstract: Dissimilatory iron reduction (DIR) plays an essential role in biogeochemical Fe cycling in anoxic environments. At near-neutral pH, in both biotic and abiotic systems, aqueous Fe(II) (Fe(II)aq ) interacts with reactive ferric (hydr)oxides via electron transfer and atom exchange that is catalyzed by large amounts of sorbed Fe(II). This may result in substantial Fe isotope exchange, which, at equilibrium, produces up to a ∼4‰ 56 Fe/ 54 Fe fractionation between coexisting oxide/hydroxide and Fe(II)aq, depending on mineralogy. The role of biology in such systems has been interpreted to lie in the production of Fe(II) rather than a specific "vital" effect, such as enzymatic and kinetic processes. Under acidic abiotic conditions, however, the lack of sorbed Fe(II) generates little Fe isotope exchange, and, by extension, it has been expected that little exchange would occur during DIR at low pH if sorbed Fe(II) is the key component for catalyzing isotopic exchange. In this study, we explored the extent and mechanism of Fe isotope exchange between Fe(II)aq and ferric hydroxides (ferrihydrite and goethite), including determination of the 56 Fe/ 54 Fe fractionations during DIR by Acidianus strain DS80 at pH ∼ 3.0 and 80 °C, over 19 days of incubation. Significant Fe(III) reduction occurred for both minerals along with large changes in Fe isotope compositions for Fe(II)aq, indicating Fe isotope exchange. Solid-phase extractions using HCl confirmed a lack of sorbed Fe(II), which suggests that a mechanism other than sorption is required to catalyze Fe isotope exchange during DIR at low pH. Reactive Fe(III) (Fe(III)reac ) extracted from the mineral surface allowed for the calculation of the Fe pools that underwent isotopic exchange. A total of ∼20% of goethite and ∼60% of ferrihydrite underwent isotopic exchange over 19 days. For goethite from biotic experiments, we calculate a Fe(III)reac -Fe(II)aq fractionation factor of 1.57 ± 0.52‰, which is larger than the abiotic equilibrium fractionation factor (∼0.73‰ at 80 °C). This result is consistent with previous work on DIR of goethite at neutral pH, where a fractionation factor larger than equilibrium was interpreted to reflect an isotopically distinct "distorted surface layer" of goethite produced during exchange with Fe(II)aq . In contrast to goethite, the difference between the Fe(III)reac -Fe(II)aq fractionation factor for ferrihydrite from our biotic reactors (2.91 ± 0.40‰) and the abiotic equilibrium fractionation factor (∼2.28‰ at 80 °C, under silica-free conditions) is smaller. Ultimately, the contrast in the extent of Fe isotope exchange between biotic and abiotic experiments emphasizes the importance of biology in promoting Fe isotope exchange in acidic systems. We speculate that the unique role of biology at low pH in catalyzing Fe isotope exchange, not seen in equivalent abiotic systems, must lie in the transport of electrons to the ferric hydroxide surface that produces Fe(II) atoms in situ . This suggests that isotopic exchange occurs on an atom-by-atom basis as Fe(III) is reduced to Fe(II), followed by the release of Fe(II) into solution. This study demonstrates that significant variations in Fe isotope compositions may be uniquely produced in acidic environments where microbial Fe cycling occurs via DIR, compared to minor isotopic variations observed previously in acidic abiotic systems.